As liberdades instrumentais de Amartya Sen e os novos indicadores de desenvolvimento - Correa Junior, Carlos Barbosa (2012)
In recent decades, as well as wealth, health, quality of life, safety or education, the concept of development reaches a new paradigm by including a key variable, represented by the question of intergenerational preservation of the environment. Thus, a modern concept of sustainable development gains strength. The concept of development is to express ethical and economic aspirations of equitable, balanced and sustainable goods and benefits, or produced and offered by the planet. It is observed, moreover, a heterogeneity in the conceptual drawing tools and indicators of the evaluation of development. In view of Amartya Sen, development is not described as an increase in aggregate income of a nation or a per capita income of the population, but as the expansion of the freedoms that individuals enjoy. The increased freedom includes both the means and the end of development, because the expansion of freedom leads to the development and the development of society, in turn, promotes increased freedoms. Amartya Sen highlights five instrumental freedoms construed as rights and opportunities that help promote overall capacity of a person: political freedoms, economic facilities, social opportunities, transparency guarantees and protective security. In this context, the general objective of this study is to comparatively study, based on archival research and bibliography, a list of new indicators of development, analyzed and synthesized from the five instrumental freedoms of Amartya Sen. The results meet the proposed objectives and may well be a model in the discussion on the construction, analysis and use of new indicators of development